ANALISA PEMANFAATAN ENERGI PADA SEPEDA LISTRIK DENGAN KAPASITAS BATERAI 38V 12Ah - Slamet Riyadi,; Muhammad Za’imul Haq,; Lily Budinurani,; Ninik Septyani, (Journal of Innovation Research and Knowledge, 2025)
Current developments in technology and mobility have encouraged humans to innovate and create means of transportation that are energy efficient, environmentally friendly and can reduce dependence on fuel oil which will eventually run out. The aim of this research is to design, make and find out how an electric bicycle works/system using a generator, battery and electric motor as a driving source, then to find out the amount of power output from the generator and find out the rotation speed of the motor with a load. different ones. Environmental information, Electrical energy consumption information, Rider weight information, Evaluating, Documentation. There are two performance criteria for this electric bicycle, namely analyzing the electrical energy of this electric bicycle by testing performance with varying road conditions, load and speed. This test method includes testing equipment and the testing stages carried out. In this test the data taken is about electrical energy consumption on an electric bicycle with 3 batteries with a voltage of 12v combined into one, power consumption information can be seen with a tool that called a watt meter which is connected to the three batteries. There are 3 riders with different weights or loads with the same distance traveled so that comparisons can be made with different weight variations. get voltage results that are not much different from the current consumption needed for an electric bicycle to run or function with a power consumption of 23.4 w. and the power output when testing without load reaches 23.9 w. With this trial, we can find out the power performance of electric bicycles on horizontal and uphill road conditions